Dyadic Essays: Enhancing Students’ Paragraph Coherence in Imaginative Writing - Nurrahma, Avinta Ika (Journal of English Teaching and Learning Issues, 2018)
This research aims to find out what improvement dyadic essay technique results in solving the problem of paragraph coherence of students’ imaginative writing. To describe how dyadic essay motivates students in doing teaching learning activity of imaginative writing in classroom. The approach used in this research is a classroom action research. The action research was conducted in two cycles, there were 4 meetings in each cycle. In collecting the data, the researcher used observation, questionnaires, interviews, and field notes as the qualitative data, and test for the quantitative data. The researcher also analyzed the mean score of each test to find out the improvements of students’ paragraph coherence in imaginative writing after the action was conducted. The mean scores of the test result are 67.42 for the pre-test, 78.09 for the post-test in cycle 1, and 86,18 for the post-test in cycle 2. The students were motivated in doing teaching-learning of imaginative writing in classroom. It was proven that the students felt enthusiastic in reading text and watching video and the students’ activeness during the teaching learning process.